Prediction of the crack growth propagation direction in non-proportional mixed-mode missions - Amato, Daniele; Mayrhofer, Lukas; Robl, Christian; Dhondt, Guido; Citarella, Roberto (International journal of fatigue, 2023)
•The Crack Growth Propagation due to Missions was investigated both experimentally and numerically.•Several Non-Proportional Mixed-Mode loading conditions were analysed.•The numerical simulations were performed with two different numerical tools: CRACKTRACER3D and FRANC3D.•The numerical results were validated with the experiments and important conclusions were drawn. The prediction of the crack growth propagation direction due to Non-Proportional Mixed-Mode missions is still an open debate in industrial applications. This study proposes two algorithms, both based on the dominant step criterion, to evaluate the cyclic crack propagation due to missions with varying mixed-mode loading conditions. They are implemented in the commercial software FRANC3D (coupled with ABAQUS) and the MTU Aero Engines AG in house tool, CRACKTRACER3D (coupled with CalculiX). The results of the numerical simulations are validated with the experimental data from tension-torsion tests with and without phase shift. The comparisons show that both software predictions are in good agreement with the experimental results and they can be confirmed as valid tools to simulate crack propagation due to a mission.